Experimental study on unregulated emission characteristics of a two-wheeler with ethanol-gasoline blends (E0 to E50). (15th February 2020) - Sakthivel, P.; Subramanian, K.A.; Mathai, Reji
Abstract: The study investigated the unregulated emission characteristics of a two-wheeler running on commercial gasoline (E0) and different ethanol-gasoline blends such as E10, E20, E30, E40 & E50. The physico-chemical properties of all the test fuels are presented. The two-wheeler was tested using chassis dynamometer for steady speed operation as well as transient emission test cycle. The emission species were measured using Fourier transform infra-red (FTIR) analyzer. Ethanol in gasoline enhances the fuel quality of the blend mainly octane number. The results indicate that carbonyls such as formaldehyde and acetaldehyde increased linearly with ethanol-gasoline blends. It is observed with ethanol-gasoline blend that acetaldehyde emission was three times higher than formaldehyde emission. The saturated hydrocarbon emissions (methane and ethane) increased with ethanol blends beyond E20. Aromatics (toluene), unburned ethanol emissions were higher with E30, E40 & E50 compared to neat gasoline and the blends. Ethene and propylene emissions were significantly higher with E40 & E50. All the unregulated emission components decreased with the increase in vehicle speed. The emission data and results presented in this paper could be useful to develop emission control strategies for two-wheelers.